2005
DOI: 10.1111/j.1532-950x.2005.00068.x
|View full text |Cite
|
Sign up to set email alerts
|

Force Plate Analysis Before and After Dorsal Decompression for Treatment of Degenerative Lumbosacral Stenosis in Dogs

Abstract: In dogs with DLS, FPA is an effective method in evaluating the response to surgical treatment. Normal propulsive force in the pelvic limbs was restored during 6 months after decompressive surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 18 publications
2
46
2
1
Order By: Relevance
“…Though kinematic and ground reaction force determination requires additional time and expertise, compared to some other forms of locomotor analysis (e.g. endpoint measures, ordinal rating scales), the data obtained is sensitive, objective and quantitative for a variety of orthopedic [14][15][16][17][18][19][20][21][22] and neurologic 1-3, 23-32 models of disease, in a variety of species.…”
Section: Discussionmentioning
confidence: 99%
“…Though kinematic and ground reaction force determination requires additional time and expertise, compared to some other forms of locomotor analysis (e.g. endpoint measures, ordinal rating scales), the data obtained is sensitive, objective and quantitative for a variety of orthopedic [14][15][16][17][18][19][20][21][22] and neurologic 1-3, 23-32 models of disease, in a variety of species.…”
Section: Discussionmentioning
confidence: 99%
“…In this condition, numerous soft and bony tissue alterations of the spine exist, leading to the often exercise-dependent compression of the cauda equina, including the nerve roots in the spinal canal running over the lumbosacral IVD and/or exiting the lumbosacral foramina (24, 25). Most dogs with DLSS are affected by an IVD protrusion and proliferative soft tissue.…”
Section: Discussionmentioning
confidence: 99%
“…An exact diagnosis of the individual’s compression pattern facilitates the successful planning of the surgical procedure. Dogs often respond well to dorsal decompression and partial discectomy, but malformations, instabilities, and bony proliferations or fragments have also been identified as factors causing clinically significant DLSS (2527). The release of foraminal stenosis may be necessary and can be performed successfully (28, 29).…”
Section: Discussionmentioning
confidence: 99%
“…The advantage to using a pressure mat walkway is that it enables the investigator to obtain data from all four feet without the need for repetitive passes (77,80). Force plate data have been used in assessing gait and time to return to normal function of the affected limb following surgery in dogs (82). Studies have also demonstrated the use of force plate and kinematic data to evaluate gait in OA dogs (75,83,84).…”
Section: Gait Analysismentioning
confidence: 99%